Colon-specific delivery of isoliquiritigenin by oral edible zein/caseate nanocomplex for ulcerative colitis treatment - Xiao, Meng; Wu, Shuyang; Cheng, Yanfen; Ma, Jiaqi; Luo, Xi; Chang, Liang; Zhang, Chen; Chen, Jianping; Zou, Liang; You, Yu; Zhang, Jinming (Frontiers in Chemistry, 2022)
Although a natural anti-inflammatory ingredient, isoliquiritigenin (ISL), plays an effective role in ulcerative colitis (UC) treatment, a series of drawbacks still limit its clinical application, including the poor solubility, instability in gastrointestinal tract, and rapid elimination rate of ISL. Zein-based NPs display the benefits on drug loading and delivery, whereas with the poor stability. In this study, an edible nano-system composed by zein/caseinate complex was fabricated for the colon-targeting delivery of ISL, to improve its colon retention and anti-UC effects. The optimized ISL loaded zein/caseinate NPs (ISL@NPs) were prepared by single-factor design by anti-solvent precipitation method, and then characterized. The improved cellular uptake of ISL@NPs on NCM460 and RAW 264.7 cells was evaluated in vitro. The colon tissue permeability and retention capacity in vivo, and the anti-UC efficacy of ISL@NPs in DSS-induce UC were implemented. As a result, ISL@NPs with the high drug loading efficiency of 9.39±0.26%, the average particle diameter of 137.32±2.54 nm, exhibited the pH-sensitive stability in the different simulated gastrointestinal buffer. Compared with free ISL, ISL@NPs showed significantly higher cellular uptake ability in NCM460 and RAW 264.7 cells. Based on in vivo imaging system, zein/caseinate NPs showed the prolonged colonic retention and the enhanced penetration into the colonic epithelium. Finally, the oral administration of ISL@NPs could effectively alleviate the UC-related symptoms, down-regulate the production of pro-inflammatory factors, and reduce the infiltration of macrophages and neutrophils in colon tissues. In this study, an oral colon-specific nano-system, composed with the natural compound and edible materials, was developed as the promising alternatives in the prevention and treatment of UC.